2014
DOI: 10.1016/j.socscimed.2014.06.042
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of streetscape audits to explanation of physical activity in four age groups based on the Microscale Audit of Pedestrian Streetscapes (MAPS)

Abstract: Ecological models of physical activity emphasize the effects of environmental influences. “Microscale” streetscape features that may affect pedestrian experience have received less research attention than macroscale walkability (e.g., residential density). The Microscale Audit of Pedestrian Streetscapes (MAPS) measures street design, transit stops, sidewalk qualities, street crossing amenities, and features impacting aesthetics. The present study examined associations of microscale attributes with multiple phy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
220
2
5

Year Published

2016
2016
2019
2019

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 186 publications
(232 citation statements)
references
References 28 publications
5
220
2
5
Order By: Relevance
“…A recent study in Recife, Pernambuco State, Brazil 30 , evaluated the same attributes of the built and social environment around schools and found that public transportation, social environment, and overall environmental score were related to active commuting to school by preschool children (3-5 years). Two studies tested the association between the environment's characteristics (by systematic observation) and walking and bicycling in adults 8,25 . However, these studies were done in cities in the United States, where the characteristics of the environment differ greatly in comparison to Brazilian cities 34 .…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…A recent study in Recife, Pernambuco State, Brazil 30 , evaluated the same attributes of the built and social environment around schools and found that public transportation, social environment, and overall environmental score were related to active commuting to school by preschool children (3-5 years). Two studies tested the association between the environment's characteristics (by systematic observation) and walking and bicycling in adults 8,25 . However, these studies were done in cities in the United States, where the characteristics of the environment differ greatly in comparison to Brazilian cities 34 .…”
Section: Discussionmentioning
confidence: 99%
“…These and other characteristics have been widely studied at different scales of influence by the built environment in cities (micro, meso, and macro), especially the scales related to transportationrelated physical activity 4,5,6,7 . Such characteristics include land use, street layout, presence and quality of sidewalks and bike lanes, access to public transportation, aesthetics, and public safety and security 4,6,7,8 .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations